Impact of HICPAC Guideline Adherence on Catheter-Associated Urinary Tract Infection Rates: Evidence from a District Hospital in Indonesia - Dian Nasution; Dona Nababan; Mido Ester Juniati Sitorus; Kesaktian Manurung; Frida Lina Tarigan (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Urinary tract infections (UTIs) are among the most common nosocomial infections, particularly affecting hospitalized patients with indwelling urinary catheters. The implementation of the Healthcare Infection Control Practices Advisory Committee (HICPAC) guidelines aims to reduce the incidence of UTIs through stringent infection control measures in hospital settings. This study aimed to examine the association between the implementation of HICPAC guidelines and the incidence of catheter-associated urinary tract infections (CAUTIs) among inpatients at Permata Hati General Hospital, Muara Bungo Regency, in 2024. A quantitative study using a quasi-experimental design was conducted at Permata Hati General Hospital from October 2024 to February 2025. The study population consisted of nursing staff and all inpatients with urinary catheters. A total of 68 respondents were included, divided equally into two groups: 34 patients before and 34 after the implementation of HICPAC guidelines. Data were collected through medical record reviews and structured questionnaires. Statistical analyses were performed using the Chi-square and Wilcoxon tests. The results showed a statistically significant association between the implementation of HICPAC guidelines and a reduction in CAUTI incidence (p = 0.040). Additionally, significant improvements were observed in nurses' knowledge, attitudes, and practices following the socialization and application of the guidelines. In conclusion, effective implementation of HICPAC guidelines significantly reduces the risk of CAUTIs in hospitalized patients. Hospitals are encouraged to strengthen nurses' adherence to infection control protocols to minimize the incidence of these infections. Keywords: Catheter Associated Urinary Tract Infection, HICPAC Guidelines, Infection Control, Hospitalized Patients, Urinary Catheters